2012
DOI: 10.1371/journal.pone.0036569
|View full text |Cite
|
Sign up to set email alerts
|

Functional Differences in Visceral and Subcutaneous Fat Pads Originate from Differences in the Adipose Stem Cell

Abstract: Metabolic pathologies mainly originate from adipose tissue (AT) dysfunctions. AT differences are associated with fat-depot anatomic distribution in subcutaneous (SAT) and visceral omental (VAT) pads. We address the question whether the functional differences between the two compartments may be present early in the adipose stem cell (ASC) instead of being restricted to the mature adipocytes. Using a specific human ASC model, we evaluated proliferation/differentiation of ASC from abdominal SAT-(S-ASC) and VAT-(V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
141
3
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(164 citation statements)
references
References 57 publications
18
141
3
2
Order By: Relevance
“…In general, across studies, SAT adipocytes were significantly larger than VAT adipocytes, irrespective of BMI or metabolic state (Liu et al, 2009;Tchernof et al, 2006), suggesting that SAT undergoes greater hypertrophy relative to VAT. However, previous studies have suggested that SAT is inherently more hyperplastic than VAT, although these observations were based on in vitro data from mouse and humans showing that SAT-derived cells have greater adipogenic capacity than VAT-derived cells (Baglioni et al, 2012;Macotela et al, 2012;Tchkonia et al, 2006). More recent in vivo data, from the transgenic AdipoChaser mouse line, have suggested the opposite: following diet-induced obesity, VAT (epidydimal) underwent waves of hyperplastic growth, whereas SAT (inguinal) did not .…”
Section: Regional Variation In Adipose Morphologymentioning
confidence: 99%
“…In general, across studies, SAT adipocytes were significantly larger than VAT adipocytes, irrespective of BMI or metabolic state (Liu et al, 2009;Tchernof et al, 2006), suggesting that SAT undergoes greater hypertrophy relative to VAT. However, previous studies have suggested that SAT is inherently more hyperplastic than VAT, although these observations were based on in vitro data from mouse and humans showing that SAT-derived cells have greater adipogenic capacity than VAT-derived cells (Baglioni et al, 2012;Macotela et al, 2012;Tchkonia et al, 2006). More recent in vivo data, from the transgenic AdipoChaser mouse line, have suggested the opposite: following diet-induced obesity, VAT (epidydimal) underwent waves of hyperplastic growth, whereas SAT (inguinal) did not .…”
Section: Regional Variation In Adipose Morphologymentioning
confidence: 99%
“…This can be illustrated by the WNT pathway, which regulates adipose tissue formation in a spatially significant manner (Longo et al, 2004;Zeve et al, 2012). In relation to gene changes, fat-storing cells derived from subcutaneous progenitors accumulate more lipid and express higher levels of PPARγ and C/EBPα upon differentiation compared with visceral progenitor cells (Baglioni et al, 2012;Tchkonia et al, 2002). Subcutaneous progenitor cells also have improved growth rate and different electrophysiological properties (Baglioni et al, 2012;Macotela et al, 2012).…”
Section: Reviewmentioning
confidence: 99%
“…In relation to gene changes, fat-storing cells derived from subcutaneous progenitors accumulate more lipid and express higher levels of PPARγ and C/EBPα upon differentiation compared with visceral progenitor cells (Baglioni et al, 2012;Tchkonia et al, 2002). Subcutaneous progenitor cells also have improved growth rate and different electrophysiological properties (Baglioni et al, 2012;Macotela et al, 2012). Collectively, there appear to be intrinsic genetic depot-specific differences in adipose stem cells that result in different adipogenic potential, genetic expression patterns, growth rates and biological properties.…”
Section: Reviewmentioning
confidence: 99%
“…To record only K þ currents without any inward Ca 2 þ current contamination we added nifedipine (10 mM) and Ni 2 þ (50 mM) to block L-and T-type Ca 2 þ current, respectively or Cd 2 þ (0.8 mM) to block both the types. To evaluate the presence of the voltage-and Ca 2 þ -dependent delayed-rectifier iberiotoxin-sensitive K þ current (I BK ), of the slowly activating chromanol-sensitive K þ current (I Ks ) and of the fast activating α-dendrotoxin-sensitive K þ current, I K(V), we performed a pharmacological dissection as previously reported (Baglioni et al, 2012). Briefly, we first applied the stimulation protocol in control condition to record the total K þ current traces (I K,tot ).…”
Section: Solutionsmentioning
confidence: 99%
“…In particular, by electrophysiological technique, we evaluated the action of melatonin on resting membrane potential and on voltage-dependent ionic channels known to play a role in proliferation (Baglioni et al, 2012;Bertolesi et al, 2002;Currò, 2014;Enomoto et al, 1986;Gamper et al, 2002;Girgert et al, 2009;Grant et al, 2009;Gray et al, 2004;Haren et al, 2010;Kunzelmann, 2005).…”
Section: Introductionmentioning
confidence: 99%